Complexos de rutênio contendo aminoácidos, com propriedades citotóxicas em células tumorais - Almeida, Marcio Aurélio Pinheiro (2009)
The synthesis of transition metal compounds mainly with ruthenium, has been increasing along the time, since compounds of this kind have many applications in the biological fields, among them, as anticancer agent. In this work were synthesized and characterized ruthenium compounds with amino acids of the general formula [Ru(AA)(dppb)(bipy)]PF6, AA = amino acid, dppb = 1,4-bis(diphenylphosphino)butane and bipy = 2, 2`-bipyridine, using as precursor the cis-[RuCl2(dppb)(bipy)]. Standard techniques were used for characterization of the complexes, among them: 31P{1H} NMR and 13C, IR, UVVis, Cyclic Voltammetry, Differential Pulse Voltammetry and X-Ray diffraction. Also, were made cytotoxicity experiments in cells of the type MDA-MB-231 to evaluate the citotoxity of the complexes. In the 31P{1H} NMR spectra of the complexes four doublets were detected with values close to 46, 44, 39 e 38 ppm with exception of the compound [Ru(Gly)(dppb)(bipy)]PF6 that presented only two doublets on 45,3 and 38,5 ppm. This suggests that there is a mixture of diastereoisomers for all compounds, with exception for the complex [Ru(Gly)(dppb)(bipy)]PF6. At the cyclic voltammetry of all compounds, except of compound [Ru(L-Met)(dppb)(bipy)]PF6 (irreversible) is observed a quasi-reversible Ru(III)/Ru(II) redox process with values close to 1100 mV. Also, there is another process of lower intensity above 1200 mV that is better observed by this differential pulse voltammetry that are attributed to redox process of the amino acids. The electronic spectra of the compounds are practically the same, showing bands around 290, 420 and 500 nm (shoulder) that are attributed to intra-ligand π→π* or to dπ(Ru)→π*(bipy) transitions. The diastereoisomers of the compound [Ru(L-Ser)(dppb)(bipy)]PF6 were separated by HPLC. These diastereoisomers were identified by circular dichroism spectroscopy (CD). Crystals of the compounds [Ru(Gly)(dppb)(bipy)]PF6 and [Ru(L-Leu)(dppb)(bipy)]PF6, were obtained and both showed the nitrogen of the amino acid to be trans to the phosphorus atom of the dppb and the oxygen opposite to the nitrogen of the bipyridine. The IC50 of all compounds in the cellular experiments with tumoral lineage were found to be lower than that one of the cisplatin, especially the IC50 of the compound [Ru(L-Met)(dppb)(bipy)]PF6 (5 μM), which is 17,5 time lower than the IC50 of the cisplatin in the same experimental condition.